Persistence of bactericidal antibodies following infant serogroup B meningococcal immunization (4CMenB) and booster dose response at 12, 18 or 24 months of age - Snape, M; Pollard, A; Voysey, M; Finn, A; Bona, G; Esposito, S; Principi, N; Diez-Domingo, J; Sokal, E; Kieninger, D; Prymula, R; Dull, P; et al. (Lippincott, Williams and Wilkins, 2015)
Background: A serogroup B meningococcal vaccine (4CMenB) is licensed for infant use in countries including Canada, Australia and those of the European Union. Data on serum bactericidal antibody (hSBA) waning and the ideal timing of a ‘toddler’ booster dose are essential to optimise vaccine utilization. Methods: An open-labeled, multicenter phase-2b follow-on European study conducted from 2009 to 2012. Participants previously receiving 4CMenB with routine vaccines at 2,4,6 or 2,3,4 months (246Con and 234Con) or at 2,4,6 months intercalated with routine vaccines (246Int) received a booster dose at 12, 18 or 24 months. 4CMenB-naïve ‘Control’ participants aged 12, 18 or 24 months received two doses of 4CMenB two months apart. Results: 1588 participants were recruited. At 12 months, prior to any booster doses, the proportions with hSBA titers ≥ 1:5 for strain 44/76-SL (testing vaccine component fHBP) were 73% (120/165) for the ‘246Con’ group, 85% (125/147) for ‘246Int’, 57% (51/90) for ‘234Con’ and 13% (26/199) for Controls. For strain 5/99 (NadA) proportions were ≥ 96% (all 4CMenB-recipients) and 1% (Controls). For strain NZ98/254 (PorA) these were 18-35% (4CMenB-recipients) and 1% (Controls). By 24 months, 4CMenB-recipient proportions were 13%–22% (44/76-SL), 82%-94% (5/99) and 7-13% (NZ98/254) and in Controls ≤ 4%. Following a 12-month booster-dose ≥ 95% of previously immunized participants had titers ≥1:5 (all strains). Conclusions: A 4CMenB booster-dose can overcome waning hSBA titers after early-infant immunization. Administration at 12 months could help to maintain immunity during an age of high risk, and the persistence of this response requires further study.